A Chiral Ligand Assembly That Confers One‐Electron O2 Reduction Activity for a Cu2+‐Selective Metallohydrogel. (23rd February 2018) - Wang, Xiaojuan; Wei, Chuanwan; Su, Ji‐Hu; He, Bo; Wen, Ge‐Bo; Lin, Ying‐Wu; Zhang, Yi
Abstract: The design of functional metallohydrogels is attractive but challenging. A rational approach is introduced for designing functional metallohydrogels using chiral ligands, a phenylalanine derivative with a pyridyl group (l /d ‐PF). Intriguingly, the as‐prepared metallohydrogel exhibits excellent O2 binding and activating properties. Insights into the O2 binding pathway reveals the presence of a novel [(l +d )‐PF‐Cu 3+ ‐O2 − ] species, which can efficiently reduce ferric cytochrome  c with the reactive O2 − by receiving an electron from reductant ascorbic acid. This study provides helpful instructions for developing new artificial systems with specific functions through the effective combination of chiral ligands with metal ions.